Introduction of folklore to improve students' storytelling skills in SD Negeri 060937 Kwala Bekala: - - Karmila Karo; Restio Sidebang (Abdimas Paspama, 2024)
Storytelling skills are the ability to retell an action or an event orally with the aim of sharing experiences or knowledge with others. Storytelling itself is one of the speaking skills. Storytelling activities form a person can convey various stories and express feelings experienced. Students can express what they want to tell and their attention in storytelling activities. In its implementation, storytelling activities require story material or ideas, mastery of the story, calmness and courage. Storytelling is one of the habits of society from ancient times until now. Almost every student who has enjoyed a story will always be ready to retell it, especially if the story is impressive to the student. One speaking skill that aims to provide information to others. It is said so because storytelling is included in informative situations that want to make understandings or meanings clear. By telling stories, a person can convey various kinds of stories, expressions of various feelings according to what is experienced, felt, seen, read and expressions of willingness and desire to share the experiences they have gained. Stories can be used by parents and teachers as a means of educating and shaping children's personalities through a cultural transmission approach and an effort to instill ethical values or character values.